Pirates of Empire Colonisation and Maritime Violence in Southeast Asia - Eklöf Amirell, Stefan (Social Sciences, 2019)
The suppression of piracy and maritime raiding was a keystone in the colonisation of Southeast Asia. This comparative study in colonial history explores how piracy was defined, contested and used to resist or justify colonial expansion, particularly from c.1850 to c.1920. This title is also available as Open Access on Cambridge Core.